2006
DOI: 10.2298/avb0606553j
|View full text |Cite
|
Sign up to set email alerts
|

Rhabdovirus carpio as a causative agent of disease in rainbow trout (Oncorhynchus mykiss - Walbaum)

Abstract: High mortality of 1-year old rainbow trout occurred on a fish farm in the spring season, with clinical symptoms typical for acute septicemia. Histological examination revealed inflammatory changes and necrosis of the internal organs. The causative agent was isolated on RTG-2 and EPC cell lines and identified by serum neutralisation, enzyme-linked immunosorbent assay (ELISA) and immunofluorescence (IFAT) as Rhabdovirus carpio. Experimental infection using the virus isolated from rainbow trout caused disease in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…In the autumn of 2007, two strains of SVCV were isolated from cultured rainbow trout fingerlings due to increased mortality (cumulative mortality around 10%) with non‐specific clinical signs, which prompted sampling and examination. Previous reports from Serbia, Iran and Northern Ireland have described the isolation of SVCV from rainbow trout (Asl et al, 2008; Jeremic et al, 2006; Rowley et al, 2001). Haenen and Davidse (1993) reported that, following experimental infection, SVCV strains did not result in significant mortalities in rainbow trout.…”
Section: Discussionmentioning
confidence: 99%
“…In the autumn of 2007, two strains of SVCV were isolated from cultured rainbow trout fingerlings due to increased mortality (cumulative mortality around 10%) with non‐specific clinical signs, which prompted sampling and examination. Previous reports from Serbia, Iran and Northern Ireland have described the isolation of SVCV from rainbow trout (Asl et al, 2008; Jeremic et al, 2006; Rowley et al, 2001). Haenen and Davidse (1993) reported that, following experimental infection, SVCV strains did not result in significant mortalities in rainbow trout.…”
Section: Discussionmentioning
confidence: 99%
“…Parameter 5 -Wild reservoir species (or family/orders) Species listed as having incomplete evidence for susceptibility to SVCV by WOAH include: spotfin shiner (Cyprinella spiloptera) (Boonthai et al, 2017) and creek chub (Semotilus atromaculatus) (Boonthai et al, 2017). SVCV has also been isolated from rainbow trout (Oncorhynchus mykiss) (Johnson et al, 1999;Jeremi c et al, 2006), crucian carp (Carassius carassius), pike (Esox lucius), fire belly newt (Cynops orientalis), silver carp (Hypophthalmichthys molitrix), yellow perch (Perca flavescens), white sucker (Catostomus commersonii), Nile tilapia (Oreochromis niloticus), emerald shiner (Notropis atherinoides), mrigal carp (Cirrhinus mrigala), tench (Tinca tinca), Chinook salmon (Oncorhynchus tshawytscha), sockeye salmon (Oncorhynchus nerka) and Pacific white shrimp (Litopenaeus vannamei) (Johnson et al, 1999).…”
Section: Reservoir Animal Speciesmentioning
confidence: 99%
“…Experimental infection of other cyprinid species included roach (Rutilus rutilius) [8], zebrafish (Danio rerio) [9], and fathead minnow (Pimephales promelas) [Emmenegger unpublished data]. Fish species from other families of Poeciliidae, Esocidae, Centrarchidae, Siluridae, and Salmonidae have also been infected by SVCV [2,10]. Due to the highly infectious nature of SVCV and potential impact this virus could have on susceptible fish populations globally, any detection of SVCV requires notification within 48 h to the Office of Internationale Epizootic (OIE), the organization charged with regulating world animal health.…”
Section: Introductionmentioning
confidence: 99%